Dukungan Sosial dan Kecerdasan Emosional Remaja - Gunawan, Surya; Alfita, Laili (Journal of Education, Humaniora and Social Sciences (JEHSS), 2024)
This article aims to examine the influence of social support on emotional intelligence among adolescents through a literature review. The issue is focused on how social support shapes emotional intelligence during adolescence, a crucial period marked by significant physical, cognitive, emotional, and social changes, as outlined in Peter's theory. These changes often make it challenging for adolescents to differentiate between positive and negative influences, which can lead to deviant behaviors. According to Hayati, high levels of social support can have a positive impact on adolescents, such as providing care, emotional support, physical assistance, problem-solving capabilities, and a sense of being valued. Goleman's theory further suggests that emotional intelligence is not a fixed trait but a psychological factor that can be developed through environmental influences. This literature review synthesizes findings from 10 selected articles, gathered from electronic databases such as Google Scholar and Science Direct, focusing on studies published in the last ten years. The analysis reveals a significant positive relationship between social support and emotional intelligence in adolescents, indicating that higher levels of social support are associated with increased emotional intelligence.